Carrion Crows Cannot Overcome Impulsive Choice in a Quantitative Exchange Task - Bugnyar, Thomas; Wascher, Claudia A.; Dufour, Valerie (Frontiers in Psychology, 2012)
The ability to control an immediate impulse in return for a more desirable – though delayed – outcome has long been thought to be a uniquely human feature. However, studies on non-human primates revealed that some species are capable of enduring delays in order to get food of higher quality or quantity. Recently two corvid species, common raven (Corvus corax) and carrion crow (Corvus corone corone), exchanged food for a higher quality reward though seemed less capable of enduring delays when exchanging for the same food type in a higher quantity. In the present study, we specifically investigated the ability of carrion crows to overcome an impulsive choice in a quantitative exchange task. After a short delay, individuals were asked to give back an initial reward (cheese) to the human experimenter in order to receive a higher amount of the same reward (two, four, or eight pieces). We tested six captive crows – three individuals never exchanged the initial reward for a higher quantity; the other three birds did exchange though at very low rates. We performed a preference test between one or more pieces of cheese in order to address whether crow poor performance could be due to an inability to discriminate between different quantities or not attributing a higher value to the higher quantities. All birds chose the higher quantities significantly more often, indicating that they can discriminate between quantities and that higher quantities are more desirable. Taken together, these results suggest that, although crows may possess the cognitive abilities to judge quantities and to overcome an impulsive choice, they do so only in order to optimize the qualitative but not quantitative output in the exchange paradigm.